Changing marriage system of Adivasi Garo Community and its impact on their socioeconomic development - Ahmed, K; Ali, RN; Begum, F (Journal of the Bangladesh Agricultural University, 2010)
The purpose of the study was to analyze the changing pattern of marriage system of Adivasi Garo community. For the study, Modhupur upazila of Tangail district for Plain Garos and Haluaghat upazila of Mymensingh district for Hill Garos were chosen as the research areas. From these two upazila, six villages were selected randomly for collecting sample population. The sample consisted of 100, taking 50 Hilly Garo respondents from three villages of Haluaghat upazila and 50 Plain Garo respondents from three villages of Modhupur upazila. Primary data were collected from the respondents through a sample survey with the help of a interview schedule. It was found that in both upazila, the essential rules for their marriage were maintained but due to conversion of Christianity, these rules are changing. A rule followed by the respondents is highest in case of a Garo should always marry a Garo (95%). Christian marriage rituals are now increasing in both upazila. Very few traditional rituals were followed by Garos for establishing their marriage. Before conversion to Christian, Garos were used to the traditional forms of marriage such as ‘Marriage by Capture’ and Thunapp’ a marriage (marriage through food offering) which has stopped now but still today it has some influences upon their marriage system. The study also revealed that most of the Garos are interested in love marriage and arranged marriage. In love marriage, Garos select their life partners themselves. After marriage, today the male Garos are not interested in moving to his wife’s parents house; rather they are living in a independent house. Moreover, while the Garo society is changing from a matrilineal to patriarchal one, this change invites many changes in their social and cultural life, such as inheritance, gender roles, post marital residence etc. The finding also showed that despite many similarities, there are very few customs and ritualistic differences between two upazilas, but comparatively Hilly Garo villages culture and tradition were changing less than the plain Garo villages. Keywords: Garo community; Hilly Garo; Plain Garo; Marriage system; Changing rules DOI: 10.3329/jbau.v8i1.6410 J. Bangladesh Agril. Univ. 8(1): 133-139, 2010